Whose Responsibility Is It? Beliefs About Preventing HIV Transmission Among Men Who Have Sex With Men. Issue 7 (July 2018) - Truong, Hong-Ha M.; Fatch, Robin; Tan, Judy Y.; Raymond, H. Fisher; McFarland, Willi
Abstract : Abstract: HIV-negative and HIV-positive men believed that they both are responsible for preventing HIV. Responsibility beliefs, however, did not always correspond with discussing HIV status or refraining from serodiscordant condomless anal sex. Discrepancies between individuals' HIV prevention responsibility beliefs and their sexual risk behaviors merit further examination, particularly in the preexposure prophylaxis era. Abstract : HIV-negative and HIV-positive men believed that they both have a responsibility for preventing HIV. Their sexual risk behavior, however, did not correspond with their prevention responsibility beliefs.